La asfixia y su relación con la identificación del fenómeno del diente rosado en Odontología forense. - Aguilar Mejía, Melany Nicole (2025)
The pink tooth is a non-specific thanatological phenomenon and sign that depends on certain factors such as humidity, age, position of the body, time elapsed, and the cause of death. It is generally associated with deaths due to asphyxiation, where various pathophysiological events occur that particularly cause the anterior teeth to turn a pinkish-red color. This research was conducted to analyze the relationship between asphyxiation and the pink tooth phenomenon in forensic dentistry. A literature review was carried out using scientific articles, books, and theses specialized in Dentistry and Forensics, focusing on the analysis of asphyxiation and its relationship with the identification of the pink tooth phenomenon. The sources of information were obtained from databases such as PubMed, Elsevier, Scielo, and Google Scholar. The PRISMA methodology (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) was used to ensure a high-quality literature review, guaranteeing transparency and reproducibility in the process of searching, selecting, and synthesizing relevant studies. Finally, after applying the selection criteria, 37 scientific documents were analyzed. After an exhaustive study, it was established that the pink tooth phenomenon has not achieved maximum value in the forensic field because it has been considered a non-specific thanatological sign. However, its appearance is closely related to the pathophysiological characteristics resulting from asphyxiation. Additionally, this phenomenon in asphyxial deaths does not occur in isolation, as anatomical, physiological, environmental, and temporal factors influence its appearance. Regarding the histological changes associated with asphyxiation that occur around dental tissues, it is concluded that these are conditions that can improve the interpretation of the circumstances and conditions of an individual's death. Therefore, the pink tooth phenomenon is a postmortem manifestation that, although a non-specific sign with respect to the cause of death, serves as a guiding indicator in forensic sciences.